Plasmodium knowlesi and wuchereria bancrofti: their vectors and challenges for the future - Vythilingam, Indra (2012)
Malaria and filariasis still continue to pose public health problems in developing countries of the tropics. Although plans are in progress for the elimination of both these parasitic vector borne diseases, we are now faced with a daunting challenge as we have a fifth species, Plasmodium knowlesi a simian malaria parasite affecting humans. Similarly in peninsular Malaysia, filariasis was mainly due to Brugia malayi. However, we now see cases of Wuchereria bancrofti in immigrant workers coming into the country. In order to successfully eliminate both these diseases we need to know the vectors involved and introduce appropriate control measures to prevent the diseases occurring in the future. As for knowlesi malaria it is still uncertain if human to human transmission through mosquito bites is occurring. However, P. knowlesi in human is not a rare occurrence anymore and has all the characteristics of a pathogen spreading due to changes in the ecosystem, international travel, and cross border migration. This has created a more complex situation. In order to overcome these challenges we need to revamp our control measures. This paper reviews the vectors of malaria and filariasis in Southeast Asia with special emphasis on P. knowlesi and W. bancrofti in Malaysia and their control strategies.